Water structure and solvation of osmolytes at high hydrostatic pressure: pure water and TMAO solutions at 10 kbar versus 1 bar. Issue 37 (7th October 2015) - Imoto, Sho; Forbert, Harald; Marx, Dominik
<x xml:space="preserve">Abstract</x> Solvation structures of trimethylamine N-oxide change drastically due to the increase in the hydrostatic pressure.